2013
DOI: 10.1111/1574-6968.12094
|View full text |Cite
|
Sign up to set email alerts
|

Salinibacter: an extremely halophilic bacterium with archaeal properties

Abstract: The existence of large number of a member of the Bacteroidetes in NaCl-saturated brines in saltern crystallizer ponds was first documented in 1999 based on fluorescence in situ hybridization studies. Isolation of the organism and its description as Salinibacter ruber followed soon. It is a rod-shaped, red-orange pigmented, extreme halophile that grows optimally at 20-30% salt. The genus is distributed worldwide in hypersaline environments. Today, the genus Salinibacter includes three species, and a somewhat le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 77 publications
2
42
0
2
Order By: Relevance
“…For instance, significant expression levels were detected for complete Embden-Meyerhof glycolysis, including fructose-1,6-bisphosphate aldolase, whose activity was not detected previously (33). Alternative glucose degradation by the Entner-Doudoroff pathway presented decreasing expres- sion levels from the first reaction, supporting the lack of activity of 2-keto-3-deoxy-6-phosphogluconate aldolase reported previously (34).…”
Section: Resultssupporting
confidence: 79%
“…For instance, significant expression levels were detected for complete Embden-Meyerhof glycolysis, including fructose-1,6-bisphosphate aldolase, whose activity was not detected previously (33). Alternative glucose degradation by the Entner-Doudoroff pathway presented decreasing expres- sion levels from the first reaction, supporting the lack of activity of 2-keto-3-deoxy-6-phosphogluconate aldolase reported previously (34).…”
Section: Resultssupporting
confidence: 79%
“…S1 in the supplemental material). Perhaps this was because of their high degree of adaptability to hypersaline waters (1,70). Other phyla abundant in six of the lakes (with Lake Gasikule being the exception) were Proteobacteria, Actinobacteria, Verrucomicrobia, and Planctomycetes.…”
Section: Discussionmentioning
confidence: 99%
“…They are distributed in hypersaline waters worldwide and are frequently dominant (69,70). Unclassified class At12OctB3 within the Bacteroidetes, which was detected for the first time in a hyper- saline lake (1), comprised 3.7 to 8.3% of the sequences in each sequencing library for Lake Gasikule.…”
Section: Discussionmentioning
confidence: 99%
“…In the present inquest red coloured colonies were used for further analysis. The study based on extremely halophilic Archaea are capable of producing red pigments known as carotenoids which gives red, yellow and orange colour to the organism and also to compact the high salt and intense UV radiation [15]. It was shown that these colored pigments have strong antioxidant, immune boosting activities and protecting premature ageing [16].…”
Section: Isolation and Screeningmentioning
confidence: 99%